Analisis Kemudahan Akses Pelayanan Administrasi dengan Didukung oleh Komunikasi yang Efektif di Kantor Camat Lolofitu Moi Kabupaten Nias Barat (Jurnal Riset Manajemen dan Akuntansi, 2025)
This study is entitled "An Analysis of the Ease of Access to Administrative Services Supported by Effective Communication at the District Office of Lolofitu Moi, West Nias Regency." The purpose of this research is to identify and analyze the level of ease of access to administrative services, as well as to examine the role of effective communication in improving access to these services for the community in Lolofitu Moi District. This study uses a qualitative method, with data collected through interviews, observation, and documentation. The results of the research show that administrative services at the District Office of Lolofitu Moi have become more open and accessible to the public, although there are still obstacles such as limited facilities, a shortage of service personnel, and delays in service processes. On the other hand, communication between staff and the public has been fairly good and effective, particularly in terms of delivering information directly or through village officials. However, there is still a need to improve digital information dissemination to ensure faster and more equitable service. Therefore, it is recommended that the District Office enhance its facilities, strengthen staff communication training, and utilize information technology to expand the reach of its services to the community.